The Cod War Between Canada and France - Pharand, Donat (Revue générale de droit, 1987)
In January 1987, Canada and France concluded an interim “arrangement” relating to French fishing off the east coast of Canada. This caused considerable public debate and confusion. The present Note studies the content of that arrangement, as well as the main provisions of the Fisheries Agreement of 1972 which constitutes the basis for all French fishing rights off the east coast.